A Chinese Cross-Sectional Study on Symptoms in Aging Males: Prevalence and Associated Factors. Issue 2 (March 2019) - Li, Hongjun; Zhang, Xinyu; Wang, Haibo; Yang, Bin; Li, Ni; Ji, Zhigang
The Aging Male Symptoms (AMS) scale is a questionnaire designed for assessing health-related quality of life and aging-related symptoms in men. Additional knowledge of the severity of aging symptoms in males revealed by high AMS scores and the factors associated with it in the Chinese population is required. A nationally representative prevalence and risk factor estimate of AMS scores was performed to identify the associated factors for AMS severity in China. Men aged between 35 and 70 years were recruited at 33 study centers in 21 provinces, 4 municipalities, and 4 autonomous regions. The prevalence of high AMS scores and its association with demographic, anatomical, lifestyle, and clinical variables were evaluated. Chi-square tests and logistic regression models were used for analysis. Odds ratios (ORs) and 95% confidence intervals were calculated. In this study, 918 of 9, 164 (10%, p < .001) men aged between 35 and 70 years, had AMS scores ≥50. Univariate and multivariable analyses showed that an age of >40 years, poor marital relations, type 2 diabetes mellitus (T2DM), history of fracture, and smoking ≥25 cigarettes per day were the major factors that were associated with the severity of AMS (OR ≥2; p < .05). Hypertension, low income, a low education level, alcohol consumption, lack of exercise, and a waist-to-hip ratio ≥0.9 were also moderately associated with AMS severity (OR 1–2; p < .05). The current study revealed the nationally representative prevalence of severe AMS scores in Chinese men and the factors associated with severe AMS. Antiaging intervention studies should target men with specific associated factors.